Studi Komparasi Seting Tempat Aktivitas di Lingkungan Perumahan Kawasan Perdesaan Pegunungan - Cut Nuraini (Tesa Arsitektur, 2020)
A residential area has its own character according to the cultural background of the community. The residential area in Hutagodang and Habincaran has a unique arrangement in terms of placing several public facilities as places of community activity. This study aims to find out what the setting of activities in the residential area of mountainous countryside/rural areas, especially in Hutagodang and Habincaran, than comparing with previous research in Singengu. This research is a explorative-qualitative research with descriptive analysis. The data collection technique was carried out through a mini-tour to collect a number of field facts related to the settings for the activities recorded in the logbook and field sketchbooks. The results showed that the setting of activities in the residential area of Hutagodang and Habincaran villages can be grouped into two major parts, namely 1) places of worship, and 2) places of gathering. The place of worship for men is the mosque, and the setting is in the western area from alaman bolak/the center of the residential area, while the place of worship for women is the prayer room/musholla, and the setting is nearby of alaman bolak as centre area. The gathering place for men is lopo (coffee shop) whose settings are nearby of alaman bolak, precisely on the west side, while the gathering place for women is parjagalan (warung) whose settings are located east of the center of alaman bolak. Men and women have separate settings for activity, but there is one place that is used together as a gathering place, the center of the environment called alaman bolak (large yard).